The “healthy immigrant” effect: does it exist in Europe today? (Italian Journal of Public Health, 2012)
Several studies, carried out mainly in the United States and Canada, have suggested that recent immigrants are generally healthier than native-born populations in spite of the fact that they frequently have a lower socioeconomic status and less access to healthcare services. This “epidemiological paradox” has been called the “healthy immigrant” effect and is usually attributed to a self-selection process prior to migration, “cultural buffering” and official health screening and employability in receiving countries. In this paper, we have evaluated the European scientific research into the existence of the “healthy immigrant” effect.
Keywords: Immigration; Healthy immigrant effect; Europe